The effect of bovine bone scaffold on the microscopic biological response of human chondrocytes - Abdul Halim, Shibghatullah (2008)
Introduction In the production of cartilaginous tissue, the choice of appropiate scaffold remains as a great challenge. The currently available scaffold, either natural or synthetic still does not meet the requirement of a scaffold for cartilage tissue engineering. An ideal scaffold has to provide a mechanical stability to the individual cell as a construct or transitional framework before synthesis of new extra cellular matrix. Objective The aim of this study was to evaluate bovine bone as a tissue engineering construct for cartilage reconstruction and to investigate the biological effects of bovine bone on human chondrocyte in vitro. Method Human chondrocytes were cultured and seeded onto bovine bone scaffold with seeding density of 1 x 1 05 cells per 100 ul I scaffold and incubated for 1 day, 2 days, 5 days and 7 days. Proliferation and viability of the cells were measured by mitochondrial dehydrogenase activity (MTT assay), adhesion study was analyzed using Scanning Electron Microscopy (SEM) and differentiation study was analyzed by lmmunoflorescent staining using Confocal Laser Scanning Electron Microscopy (CLSM). Result The data showed the presence of proliferation and viability of the cells on the scaffolds by MTT method within 24 hours to 7 days observed. SEM pictures revealed presence of chondrocytes located on the scaffolds, showed increasing number of cell within the days and that cells readily grew on the surface and into the open pores of the scaffold. lmmunoflorescent staining detected collagen type II on the scaffolds which was increasing within the days. Conclusion The results showed the potential of bovine bone as three dimensional scaffold for cartilage tissue engineering because of the good cells proliferation, attachment, maturity, non toxic, safe, easily resourced and relatively cheap.